EVALUASI FASILITAS KESEHATAN DAN KESELAMATAN PADA RUMAH SUSUN DI SURABAYA - Ria A. A. Soemitro; Hitapriya Soeprayitno; Farida Rachmawati (Simposium II UNIID 2017, 2017)
The growth of industries that absorb numerous employees from outside Surabaya Metropolitan Area has led to a housing provision problem, particularly for migrant workers. The Ministry of Public Works and Public Housing and the local government have initiated construction of both rental and ownership of low-cost apartments One of some regulations regarding the low-cost apartments is focused on the building standard to ensure the occupants’ health and safety. This paper provides an assessment on the structural living conditions of selected low-cost apartment in Surabaya and the associated health and safety conditions of the inhabitants. The secondary data of housing backlog were provided from East-Java Provincial Body of Planning and Development, while the regulation and technical standard variables as the comparison parameters were obtained from literature review studies. The comparison parameters to investigate the low-cost apartment implementation were then validated by 6 purposive sampling respondents from management team and 30 random sampling respondents from occupants. These unconfirmed variables were then identified and analyzed using descriptive statistic. During the inspection, all fire extinguisher are non-operational, the access way is used for parking lot, the behaviour of the occupants is unsafe and lack of law enforcement for the indiscipline occupants. The results of this survey revealed that the infrastructure condition and the unsafe behaviour are risky to fire disaster.